Ecospiritual Praxis: Cultivating Connection to Address the Climate Crisis - Bock, Cherice (Religions, 2024)
This article suggests ecospirituality as a connection point between religion, science, and other disciplines, as well as the relationships between people, the land and waters, the community of all life, and the Divine. Ecospirituality connects different disciplines and highlights the interconnectedness between people and the rest of the natural world, and it also catalyzes action through spiritual experience and meaning-making. A review of different disciplines’ research on ecospirituality is provided. A description of an ecospiritual praxis cycle is offered, based on interviews and survey data. This ecospiritual praxis cycle may be able to help move people toward practical and efficacious actions of care for the community of all life to participate in the collective transformation that needs to occur in order to address the climate and ecological crises. This article identifies disconnection between theory and action regarding climate and environmental knowledge and collective action as one of the main problems, which “undisciplining” religion and science can help overcome.